The role of social support on HIV testing and treatment adherence: A qualitative study of HIV-infected refugees in southwestern Uganda. Issue 8 (3rd August 2017) - Rouhani, Shada A.; O'Laughlin, Kelli N.; Faustin, Zikama M.; Tsai, Alexander C.; Kasozi, Julius; Ware, Norma C.
ABSTRACT: Little is known about the factors that encourage or discourage refugees to test for HIV, or to access and adhere to HIV care. In non-refugee populations, social support has been shown to influence HIV testing and utilisation of services. The present study enrolled HIV-infected refugees on anti-retroviral therapy (ART) in Uganda, who participated in qualitative interviews on HIV testing, treatment, and adherence. Interviews were analysed for themes about four types of social support: emotional, informational, instrumental, and appraisal support. A total of 61 interviews were analysed. Four roles for these types of social support were identified: (1) informational support encouraged refugees to test for HIV; (2) emotional support helped refugees cope with a diagnosis of HIV; (3) instrumental support facilitated adherence to ART and (4) after diagnosis, HIV-infected refugees provided informational and emotional support to encourage other refugees to test for HIV. These results suggest that social support influences HIV testing and treatment among refugees. Future interventions should capitalise on social support within a refugee settlement to facilitate testing and treatment.